2023
DOI: 10.1002/dc.25136
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of endoscopic ultrasound‐guided fine needle aspiration cytology versus endoscopic biopsy for the diagnosis of subepithelial lesions of the upper and lower gastrointestinal tract: A 10‐year retrospective single institution analysis

Abstract: Background The aim of this study is to compare the diagnostic accuracy of endoscopic ultrasound‐guided fine needle aspiration (EUS‐FNA) versus endoscopic biopsy for the diagnosis of gastrointestinal (GI) subepithelial lesions (SELs) using surgical resection as the gold standard. Methods All patients who underwent EUS‐FNA of upper and lower GI SELs over a 10‐year period (2010 through 2019) were retrospectively reviewed. The medical records of all patients were reviewed and data extracted from the endoscopy, pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Although a previous study confirmed that mucosal incision-assisted biopsy is superior to ultrasound-guided fine-needle aspiration biopsy in diagnosing small lesions in the upper and lower layers of the stomach [ 18 ], EUS-guided aspiration biopsy may still be preferred in the colon, especially when space-occupying lesions make mucosal resection difficult. Moreover, the pathological results for the EUS-guided sampling and endoscopic resection of lesions are highly consistent, and fewer complications are associated with EUS-guided sampling [ 19 , 20 ]. When diagnosing subepithelial lesions, EUS-FNB often requires fewer passes than EUS-FNA [ 21 ].…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…Although a previous study confirmed that mucosal incision-assisted biopsy is superior to ultrasound-guided fine-needle aspiration biopsy in diagnosing small lesions in the upper and lower layers of the stomach [ 18 ], EUS-guided aspiration biopsy may still be preferred in the colon, especially when space-occupying lesions make mucosal resection difficult. Moreover, the pathological results for the EUS-guided sampling and endoscopic resection of lesions are highly consistent, and fewer complications are associated with EUS-guided sampling [ 19 , 20 ]. When diagnosing subepithelial lesions, EUS-FNB often requires fewer passes than EUS-FNA [ 21 ].…”
Section: Clinical Applicationsmentioning
confidence: 99%